Peran OSIM dalam Meningkatkan Kedisiplinan Ibadah Siswa di MAN 2 Labuhanbatu Utara - Fernanda, Muhammad Rifqih; Darlis, Ahmad (MODELING: Jurnal Program Studi PGMI, 2024)
This study aims to describe the role of OSIM in improving student worship discipline at MAN 2 Labuhanbatu Utara. This study uses a qualitative method with descriptive analysis. The sources of informants are the principal, supervising teacher, OSIM chairman and students. The data collection techniques are carried out through observation, interviews, and document studies. The data analysis techniques used in this study are data reduction, data display, and drawing conclusions. The results of this study indicate that the strategic role in improving student discipline through programs such as congregational Dhuhur prayers, Yasin memorization programs and prayers every Saturday, Islamic studies or lectures, Alms every Friday. OSIM also acts as a role model for students in carrying out religious values. Supporting factors for the role of OSIM include support from the school and teachers, while the inhibiting factor is the lack of student awareness in worshiping regularly.